Determination of pK(a) Values of Some Benzoxazoline Derivatives and the Structure-Activity Relationship - ÇELİK, MELEK ŞİRİN (AMER CHEMICAL SOC, 2013)
The acid ionization constant (pK(a)) values of 2-(3H)-benzoxazolinone and its 17 derivatives were determined in buffered solutions by UV-vis spectrophotometry, potentiometry, and capillary zone electrophoresis techniques. The pK(a) values of the studied compounds are found to be in the range of 9.01 to 7.15. The advantages and limitations of each technique are discussed. The results suggest that the removal of a proton from the molecule occurred on the nitrogen atom of the 2-(3H)-benzoxazolinone ring and the analgesic/anti-inflammatory activities of the benzoxazolinone derivatives decrease when the pK(a) values of the compounds increase.
Keywords: ANALGESIC ACTIVITY; MANNICH-BASES; ELECTROPHORESIS; DAMAGE